PENGARUH KUALITAS PRODUK, HARGA DAN CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN SMARTPHONE APPLE DI IBOX GANDARIA CITY - Lucy Nancy Simatupang; Irene Marsella (Jurnal Manajemen, 2021)
This study aims to determine the effect of Product Quality, Price, and Brand Image on Apple purchasing decisions at Ibox Gandaria City partially or simultaneously. The data used is primary data collected through distributing questionnaires to 100 respondents who have visited and bought at Ibox Gandaria City. The method used in this study is a quantitative method and the results of the study are based on respondents' answers using the Ordinal scale. The data analysis method used in this research is Multiple Linear Regression Test, F Test, t Test and Coefficient of Determination. The results showed that simultaneously (F test) there was a significant effect between Product Quality (X1), Price (X2), Brand Image (X3) variables on Purchase Decision (Y). Partially (t-test) Product Quality and Brand Image have a significant influence on purchasing decisions. While the price has no significant effect on purchasing decisions.